2002
DOI: 10.3354/ame028013
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial activity and genetic richness along an estuarine gradient (Rhone River plume, France)

Abstract: Bacterial diversity and activity were simultaneously investigated by microbial ecological and molecular biological methods along an estuarine gradient from the Rhone River to the Mediterranean Sea. Following a Lagrangian strategy, we sampled plume, frontal and marine layers. The sampled estuarine gradient exhibited large changes both in physico-chemical and in microbiological characteristics. Bacterial abundances and activities showed a more drastic decrease in the low salinity range of the gradient than expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
94
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(112 citation statements)
references
References 44 publications
15
94
2
1
Order By: Relevance
“…Furthermore, higher abundance of AOA was shown in the bulk community in comparison to the potentially active community. Such discrepancy between DNA-and RNA-based studies of surface waters has also been observed in freshwater ecosystems [4,68]. The denitrification genes nirK and nosZ were slightly higher in the oxic zone than in the anoxic zone (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, higher abundance of AOA was shown in the bulk community in comparison to the potentially active community. Such discrepancy between DNA-and RNA-based studies of surface waters has also been observed in freshwater ecosystems [4,68]. The denitrification genes nirK and nosZ were slightly higher in the oxic zone than in the anoxic zone (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…Freshwater and marine bacterioplankton communities typically show limited overlap in composition (Troussellier et al, 2002;Selje and Simon, 2003), whereas estuaries appear as mixing zones. However, given the location of the sampling station far from any river mouth, direct influence of advected freshwater bacteria on the indigenous bacterioplankton community is unlikely (Riemann et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, other techniques are more appropriate in situations requiring high sample numbers, for example when examining biological and/or environmental variability. Fortunately, the DNA vs RNA approach is equally applicable to high-throughput community fingerprinting techniques such as denaturing gradient gel electrophoresis Troussellier et al, 2002), terminal restriction fragment length polymorphism (T-RFLP) ) and single-stranded conformational polymorphism (SSCP) (West et al, 2008;Rodriguez-Blanco et al, 2009). It could also be used in conjunction with next-generation sequencing methods such as tag pyrosequencing (Sogin et al, 2006;Huse et al, 2008).…”
Section: U N C E R T L I N E a G E S P I R O C H A E T E S B A C T mentioning
confidence: 99%
“…The analysis of 16S rRNA genes through clone libraries and fingerprinting approaches such as denaturing gradient gel electrophoresis (DGGE) has greatly extended our knowledge about the phylogenetic richness of sponge-associated bacteria and archaea (Webster et al, 2001(Webster et al, , 2004Hentschel et al, 2002;Taylor et al, 2004Taylor et al, , 2007bHolmes and Blanch, 2006;Longford et al, 2007;Schmitt et al, 2007Schmitt et al, , 2008Thiel et al, 2007;Mohamed et al, 2008b;Zhu et al, 2008). Researchers in other systems have taken this approach one step further, yielding insights into both richness and activity by comparing 16S rRNA gene-and 16S rRNA-derived sequences, respectively (Moeseneder et al, , 2005Winter et al, 2001;Troussellier et al, 2002;Mills et al, 2005;Gentile et al, 2006;Martinez et al, 2006;Brinkmann et al, 2008;McIlroy et al, 2008;West et al, 2008;Rodriguez-Blanco et al, 2009). In general, cellular concentrations of rRNA are correlated with growth rate and activity (DeLong et al, 1989;Poulsen et al, 1993), hence-with acknowledgement of certain caveats (e.g., for ammoniaoxidizing bacteria; Morgenroth et al, 2000)-the rRNA itself can yield useful information about which community members are active.…”
Section: Introductionmentioning
confidence: 99%